Tuberculosis notification: Facilitators and barriers among private practitioners in Trichy, South India - Prabha Thangaraj; Kumarasamy Hemalatha (Wolters Kluwer Medknow Publications, 2021)
Context: The framework for tuberculosis (TB) notification is one of the components of the World Health Organization's End TB strategy. Notification is essential for estimating the true burden of TB and its control in community which is currently lacking in the private health sector. Aims: The objectives are to identify awareness, willingness, barriers, and preferred methods of TB notification among private practitioners (PPs) in Trichy, South India. Methods: A descriptive cross-sectional study was conducted among 152 doctors working in the private sector and having at least 1 year of clinical experience using nonprobability sampling. A semi-structured, pretested questionnaire was used to obtain details about the general profile, awareness, and willingness regarding TB notification, as well as factors that facilitate and hinder it. Results: Among PPs, 90.7% referred TB cases/suspects to other health facilities and 71.7% were aware that TB notification is mandatory. Only 52.6% and 38.2% were ready to provide the patients' Aadhaar number and bank account details respectively during notification. The most common barriers for notification were: not being aware about the notification procedure (50.7%), lack of time (32.2%), process being tedious (29.6%) and difficulties in getting information from patients (25.7%). Mobile SMS/App/call (74.3%) were preferred by PPs over notification through online (32.2%) and government health staff (26.3%). Conclusions: Although three-fourth of the practitioners were aware and willing to notify TB, more than half of them were not aware about the notification procedure. Improving the awareness on the techniques for notification could motivate PPs to notify TB.